An investigation into a micro-sized droplet impinging on a surface with sharp wettability contrast - Lam, Yee Cheong (2015)
An experimental investigation was conducted into a micro-sized droplet jetted onto a surface with sharp wettability contrast. The dynamics of micro-sized droplet impingement on a sharp wettability contrast surface, which is critical in inkjet printing technology, has not been investigated in the literature. Hydrophilic lines with line widths ranging from 27 to 53 µm, and contact angle ranging from 17° to 77°, were patterned on a hydrophobic surface with a contact angle of 107°. Water droplets with a diameter of 81 µm were impinged at various offset distances from the centre of the hydrophilic line. The evolution of the droplet upon impingement can be divided into three distinct phases, namely the kinematic phase, the translating phase where the droplet moves towards the centre of the hydrophilic line, and the conforming phase where the droplet spreads along the line. The key parameters affecting the conformability of the droplet to the hydrophilic line pattern are the ratio of the line width to the initial droplet diameter and the contact angle of the hydrophilic line. The droplet will only conform completely to the hydrophilic pattern if the line width is not overly small relative to the droplet and the contact angle of the hydrophilic line is sufficiently low. The impact offset distance does not affect the final shape and final location of the droplet, as long as part of the droplet touches the hydrophilic line upon impingement. This process has a significant impact on inkjet printing technology as high accuracy of inkjet droplet deposition and shape control can be achieved through wettability patterning.